Bridging Corruption Articles” through the National Criminal Code: The Perspective of Corruption Eradication and Ta'zir - Fadhil, Moh.; Anwar, M. Ian Hidayat; Fernando, Zico Junius; Anditya, Ariesta Wibisono (Al-'Adl, 2024)
One of the tasks of criminal law reform is to consolidate criminal law provisions that are scattered in various laws and regulations. The drafting team has incorporated several special offences into the National Criminal Code as a bridge between the norms, making the National Criminal Code the epicentre. This raises normative questions about the position of special offences, especially corruption offences, when the norms are shifted to general norms in the National Criminal Code, in relation to the systematic enactment of Book I of the National Criminal Code, and whether the changes in the criminal formulation are proportional to the spirit of eradicating corruption. This research will focus on answering the above-mentioned normative concerns. This type of research is a normative research that focuses on the content analysis of legal materials in the form of Book I of the National Criminal Code, articles on corruption in the National Criminal Code and the Corruption Act. The validation process of the analysis results was presented in a forum group discussion with several legal aid organisations and university research institutions. The results of the research show that the intention of the drafting team to include corruption offences is limited to the technical consolidation of corruption offences in the National Criminal Code in the form of bridging articles. In the context of the fight against corruption, there are five crucial reservations, namely the disparity of penalties, the categorisation of fines, the powers of the State Loss Calculation Institution, the stagnation of the regulation of bribery offences and the harmonisation of the United Nations Convention against Corruption.